Melanoma-derived versican reactivates tumor-associated macrophages by upregulating pyruvate carboxylase through TLR2-MyD88-RelB axis under normoxia - Shu Yuxin; Zhou Linmin; Qian Jinqin; Zhu Wei-Guo (Acta Biochimica et Biophysica Sinica, 2025)
Relieving hypoxia in the tumor microenvironment (TME) promotes innate and adaptive immunity. Our previous research demonstrated that reoxygenation of the TME promotes the phagocytosis and tumor-killing functions of tumor-associated macrophages (TAMs) by upregulating pyruvate carboxylase (PCB). However, the mechanism remains obscure. In the present study, we find that versican derived from melanoma cells binds to TLR2 and activates the downstream transcription factor RelB, which transcribes PCB under normoxia. Blocking the versican-TLR2-MyD88-RelB axis not only reverses the upregulation of PCB in TAMs but also hinders the clearance of tumor cells by TAMs. Our work suggests a pathway that modulates the functions of TAMs under normoxia, which could be harnessed for strengthening anti-tumor immunity.